2023
DOI: 10.1242/bio.059965
|View full text |Cite
|
Sign up to set email alerts
|

Preferential killing of melanoma cells by a p16-related peptide

Abstract: We report the identification of a synthetic, cell-penetrating peptide able to kill human melanoma cells efficiently and selectively, while less toxic to normal human melanocytes and nontoxic to human fibroblasts. The peptide is based on the target-binding site of the melanoma suppressor and senescence effector p16 (INK4A, CDKN2A), coupled to a cell-penetrating moiety. The killing is by apoptosis and appears to act by a route other than the canonical downstream target of p16 and CDK4, the retinoblastoma (RB) fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The research by Soo et al published in 2023 reported the identification of a synthetic peptide capable of cell penetration and induction of apoptosis of neoplastic melanoma cells in an efficient and selective manner, with the advantage of lower toxicity to normal melanocytes and absence of human fibroblasts [38]. This peptide is based on the targetbinding site of the p16 effector involved in senescence and suppression of melanoma progression, combined with a fraction that facilitates intracellular penetration [39].…”
Section: Discussionmentioning
confidence: 99%
“…The research by Soo et al published in 2023 reported the identification of a synthetic peptide capable of cell penetration and induction of apoptosis of neoplastic melanoma cells in an efficient and selective manner, with the advantage of lower toxicity to normal melanocytes and absence of human fibroblasts [38]. This peptide is based on the targetbinding site of the p16 effector involved in senescence and suppression of melanoma progression, combined with a fraction that facilitates intracellular penetration [39].…”
Section: Discussionmentioning
confidence: 99%